Prevalence study of dermatoses referred to the phototherapy unit at the Dermatology Service of the Clinics Hospital of Porto Alegre, RS, Brazil Estudo de prevalência das dermatoses encaminhadas ao setor de fototerapia do ambulatório de dermatologia do Hospital de Clínicas de Porto Alegre, RS, Brasil - Carolina Casara; Leticia Eidt; Vivian Cunha (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Phototherapy consists of exposure to ultraviolet radiation for therapeutic reasons. Radiation is already used in dermatological practice, and many studies have already proved the beneficial effect of UV light treatment for chronic inflammatory or lymphoproliferative skin diseases. The Dermatology Service of the Clinics Hospital of Porto Alegre (Hospital de Clínicas de Porto Alegre) has been using phototherapy for a long time, and no official data have been described so far. OBJECTIVES: To study the prevalence of dermatoses referred to the phototherapy unit at the Clinics Hospital of Porto Alegre and describe the total number of patients who have already been referred to this sector and their phototype. METHODS: This is a descriptive cross-sectional study. Data were collected through a review of the phototherapy patients' records (secondary data), which are available on a database of the Dermatology Service of the Clinics Hospital of Porto Alegre, from August 1997 to July 2011. RESULTS: A total of 653 records were analyzed. Phototype 3 was the most prevalent (n=313). Distribution of the prevalence of dermatoses referred to the phototherapy unit was as follows: vitiligo (279), psoriasis (255), cutaneous T-cell lymphoma/mycosis fungoides (29), graftversus-host disease (15), scleroderma (11), atopic dermatitis (10), alopecia areata (6), parapsoriasis (5), eczema (4), granuloma annulare (4), and others (35). As vitiligo and psoriasis were the two most prevalent dermatoses, they were analyzed separately, with no statistical difference in prevalence between them (P=0,177). CONCLUSIONS: Our findings are in accordance with the literature, showing that although phototherapy is still mostly indicated to treat psoriasis, it has been used to treat other dermatoses, since the results are promising. FUNDAMENTOS: Fototerapia é exposição à radiação ultravioleta para uso terapêutico. O uso dessas radiações já é utilizado na prática dermatológica, e estudos já provaram o efeito benéfico do tratamento UV em doenças inflamatórias crônicas ou linfoproliferativas. O Serviço de Dermatologia do Hospital de Clínicas de Porto Alegre tem disponibilizado a fototerapia para seus pacientes há um longo tempo, sem dados oficiais descritos até então. OBJETIVO: Estudar a prevalência das dermatoses encaminhadas à fototerapia do Hospital de Clínicas de Porto Alegre e descrever o número total de pacientes já encaminhados a esse setor e seu fototipo. MÉTODOS: Estudo transversal descritivo. A coleta de dados foi feita por revisão da totalidade das fichas de cadastro dos pacientes de fototerapia (dados secundários), as quais se encontram em um banco de dados no Serviço de Dermatologia do Hospital de Clínicas de Porto Alegre, de agosto de 1997 a julho de 2011. RESULTADOS: Ao todo 653 pacientes foram analisados. O fototipo 3 foi o mais prevalente (n=313). A distribuição da prevalência das dermatoses foi: vitiligo (279), psoríase (255), linfoma cutâneo de células T/ micose fungóide (29), doença do enxerto versus hospedeiro (15), esclerodermia (11), dermatite atópica (10), alopécia areata (6), parapsoríase (5), eczema (4), granuloma anular (4) e outros (35). Visto que vitiligo e psoríase foram as dermatoses mais prevalentes, eles foram analisados separadamente. Não houve diferença estatística entre as prevalências (P = 0, 177). CONCLUSÕES: Nossos resultados estão em conformidade com a literatura, e mostram que, apesar da psoríase ainda ser a principal indicação para a fototerapia, outras dermatoses estão sendo tratadas com ela, uma vez que seus resultados tem sido promissores.